Mechanically Resistant and Sustainable Cellulose-Based Composite Aerogels with Excellent Flame Retardant, Sound-Absorption, and Superantiwetting Ability for Advanced Engineering Materials - He, Chenglin; Huang, Jianying; Li, Shuhui; Meng, Kai; Zhang, Liyuan; Chen, Zhong; Lai, Yuekun (ACS sustainable chemistry & engineering, 2018)
The production of cellulose-based aerogels from the conversion of cheap and rich precursors using environmentally friendly techniques is a very attractive subject in materials chemistry. In this work, we report a facile strategy to construct flame retardant, sound-adsorption, and mechanical enhancement cellulose-based composite aerogels by the incorporation of aluminum hydroxide nanoparticles (AH NPs) into cellulose gels via an in situ sol–gel process, followed by freeze-drying to coat AH NPs on cellulose composite aerogels (AH NPs@cellulose composite aerogels). The results demonstrated that the AH NP homogeneous dispersion within cellulose aerogels and the presence of AH NPs did not have a remarkable influence on the homogeneous porous structure of cellulose aerogels when compared with cellulose aerogels prepared from the NaOH/urea/thiourea solution. The prepared composite cellulose aerogels showed excellent flame retardancy, the peak of heat release rate (PHRR) of the composite aerogels decreased significantly from 280 W/g of the control sample to 22 W/g, and total heat release (THR) of the composite aerogels decreased remarkably from 13.2 kJ/g to 1.6 kJ/g. Moreover, the incorporation of AH NP composite aerogels exhibited remarkable mechanical properties, and the compressive strength of the composite aerogels increased significantly from 0.08 to 1.5 MPa. In addition, AH NP composite cellulose aerogels have excellent sound absorption at high frequencies with a maximum sound-absorption coefficient of 1. AH NP composite cellulose aerogels have strong water and oil affinity. After immersing the samples in mixed silica nanoparticles, heptadecafluorononanoic, and fluoroalkyl silane solutions, they became superantiwetting, with a water contact angle (CA) larger than 150° and oil CA larger than 140°. In summary, this study provides a facile strategy to rationally construct flame retardant, mechanically robust, highly efficient sound-adsorption, and superamphiphobic cellulose-based composite aerogels, which have promising applications in the future as green engineering materials.